Pirate wars - Meyer, Kai.; Crawford, Elizabeth D. (New York : Margaret K. McElderry Books, 2008)
Jolly, Griffin, and other brave warriors return to battle in one last attempt to save their world from the evil Maelstrom as, despite major setbacks, they finally realize that only courage, love, and loyalty will see them through.
Keywords: Pirates; Magic; Pirates; Magic; Fantasy